2019
DOI: 10.1016/j.jvs.2018.04.036
|View full text |Cite
|
Sign up to set email alerts
|

Shear rate is a better marker of symptomatic ischemic cerebrovascular events than velocity or diameter in severe carotid artery stenosis

Abstract: In patients with >70% ICA stenosis, the shear rate is associated with the prevalence of symptomatic cerebrovascular ischemic events. A shear rate of 8000 s and above may be used as a predictor for having symptomatic cerebrovascular ischemic events. Further validation as well as further study of the pathologic mechanism connecting the high shear rate and ischemic cerebrovascular events is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…Compared with patients with carotid artery stenosis without ischemic symptoms, patients with ischemic symptoms had higher WSS proximal and at the narrowest portion of stenosis, indicating that the higher the WSS in the narrowest area, the greater the risk of plaque rupture and detachment. This is in line with the literature reporting that wall shear obtained by measuring peak systolic velocity at the narrowest portion of stenosis can be a better predictor of ischemic stroke than the degree of stricture [20,21] .…”
Section: Discussionsupporting
confidence: 92%
“…Compared with patients with carotid artery stenosis without ischemic symptoms, patients with ischemic symptoms had higher WSS proximal and at the narrowest portion of stenosis, indicating that the higher the WSS in the narrowest area, the greater the risk of plaque rupture and detachment. This is in line with the literature reporting that wall shear obtained by measuring peak systolic velocity at the narrowest portion of stenosis can be a better predictor of ischemic stroke than the degree of stricture [20,21] .…”
Section: Discussionsupporting
confidence: 92%
“…Blood flow and haemodynamic forces also affect localized thrombin generation, fibrin formation and structure. Upon activation by collagen, thrombin or high shear, a subpopulation of platelets externalize the procoagulant phospholipid phosphatidylserine (PS) and release PS-exposed microvesicles, resulting in localized thrombin generation and fibrin formation [57,58]. In contrast, platelet activation by ADP, vWF, or thromboxane A 2 does not generate procoagulant platelets.…”
Section: Static Versus Pathological Flow Conditionsmentioning
confidence: 99%
“…In clinical practice, knowledge of WSS is currently not integrated into the decision-making algorithm for the management of carotid stenosis [3]. Although an elevation of the WSS is suggested as a vulnerability factor, those preliminary results should, however, be confirmed [8,10,11]. We hope that this technique will lead to a broader validation of this biomarker as a second step.…”
Section: Limitationsmentioning
confidence: 99%
“…For these reasons, WSS could be an important factor in the vulnerability of a carotid plaque. A rough assessment of the shear rate, obtained from the peak systolic velocity with conventional spectral Doppler associated with the smallest diameter measurement, showed that it was a better predictor of ischemic stroke than the stenosis grade [11].…”
Section: Introductionmentioning
confidence: 99%